Perceived Value: Is It Important For Word of Mouth? - Ardian Fikri Rizki; Anita Dwi Kurniawati; Adhitya Ramadhany; Yolanda Masnita (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2022)
Industry 4.0 information technology, telecommunications, and computer is snowballing, and almost all people already use the internet in their daily life. Similarly, the Indonesian banking industry and the company have a technology that uses the internet in the transaction, namely internet banking with token serves as an authentication transaction to secure the transaction, plated. This research uses Relationship Marketing with associative design. The study's method of analysis used Structural Equation Modeling (SEM). Researchers collected data through questionnaires and literature studies from previous research. The findings concluded significant relationships between E-Service Quality and Perceived Value to Customer Satisfaction. Customer satisfaction also has a substantial impact on developing positive e-word of mouth. The results also found that both e-service quality and perceived value have no effect or insignificantly affect the e-word of mouth